Editorial: Special Issue on Regional Climate Studies - Leslie, Lance; Wang, Y.; Lee, D.; Lamb, P. (Springer Wien, 2008)
This special issue of Meteorology and Atmospheric Physics focuses on the wide range of regional climate studies which increasingly are being carried out around the globe. For convenience, the 20 papers in the special issue are divided into three groups embracing modeling, observational, and theoretical topics, respectively. The modeling studies include basic principles of climate modeling, ensemble size estimations, the impact of aerosols, orography, the hydrologic cycle and the carbon cycle, and the modelling of monsoons, jets and specific severe weather events such as tropical cyclones. The observational papers cover the fundamental roles of heat fluxes and moisture, documents trends in these variables over East Asia, the southwest Indian Ocean, Australia and discusses their consequences. The theoretical analyses address the important roles of teleconnections and the occurrence of extreme weather events.